Efektivitas Air Buah Lontar dalam Mempertahankan Motilitas, Viabilitas dan Daya Tahan Hidup Spermatozoa Sapi Bali - MataHine, Thomas; ., Burhanuddin; Marawali, Aloysius (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
The objective of this study was to determine the effectiveness of palmyra juice in maintaining motility,viability, and longevity of bali cattle sperm during in vitro storage. Semen collected from a four year oldbali bull had been trained to serve an artificial vagina. Good quality semen divided into four tubes to betreated with: without extender (negative control), citrate-egg yolk (citrate-EY) and coconut water-egg yolk(CW-EY) as positive control; and palmyra juice-egg yolk (PJ-EY), and then stored in a refrigerator attemperature 3 - 8oC. Each treatment was repeated five times to form 20 experimental units. The resultsshowed that up to the fourth day of storage, sperm preserved in PJ-EY had motility 44%, higher (P<0.05)than citrate-EY, CW-EY, and without extender, i.e 30%, 18%, and 0%, respectively. PJ-EY extender alsoyield sperm viability 60%, higher (P<0.05) than citrate-EY, CW-EY, and without extender i.e 50%, 32% and0%, respectively. Sperm livability achieve 11.20 days in PJ-EY, longer (P <0.05) than citrate-EY, CW-EYand without extender, i.e 9.60 days, 7.60 days , and 1.31 days, respectively. In conclusion that palmyrajuice-egg yolk extender effective to maintain motility, viability, and longevity of bali cattle sperm duringin vitro preservation.
Keywords: palmyra juice, egg yolk, motility, viability, longevity, sperm, bali cattle